1993
DOI: 10.1055/s-2007-1002093
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acidification Rate in Cultured Fibroblasts by Glucocorticoids

Abstract: A recently-developed semiconductor-based instrument, the silicon microphysiometer, allows for realtime, sensitive quantification of cellular metabolism in small numbers of cultured cells with relative case. This is accomplished by detecting the extrusion into the extracellular space of acidic metabolic products of glycolysis, respiration, and ATP hydrolysis, including lactic acid, CO2, and protons. In the present report, we use microphysiometry to observe that glucocorticoids inhibit metabolic rate (as assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Most important for this investigation, receptor activation has been shown to alter the rate at which cells release acidic metabolites in a large number of signaling pathways. Indeed, microphysiometry has been used in studies of CNTF signaling in SH-SY5Y cells (Johnson et al, 1994), kainic acid effects on hippocampal cells (Raley-Susman et al, 1992), NGF:trkA interactions (Pitchford et al, 1995), D1 and D2 dopamine receptor action (Neve et al, 1992;Bouvier et al, 1993), m1 and m3 muscarinic receptor action (Baxter et al, 1994), ACh action on the Na ϩ /K ϩ ATPase (Miller et al, 1993), PKC action (Omary et al, 1992), cAMP effects on the H ϩ /K ϩ ATPase Thibodeau et al, 1994), glucocorticoid action (Redish et al, 1993), the role of PKC ⑀ on granulocyte-macrophagecolony-stimulating factor (GM-CSF) action (Wada et al, 1993), angiotensin II action (Dickinson et al, 1994), and CC-chemokine receptor action (Samson et al, 1996). The microphysiometer also has been used recently to examine the interactions between synthetic peptides and cognate receptors in an effort to design effective competitive inhibitors (Renschler et al, 1995).…”
Section: Bdnf Signal Transduction By Trkbt1 and Trkbt2: Microphysiomentioning
confidence: 99%
“…Most important for this investigation, receptor activation has been shown to alter the rate at which cells release acidic metabolites in a large number of signaling pathways. Indeed, microphysiometry has been used in studies of CNTF signaling in SH-SY5Y cells (Johnson et al, 1994), kainic acid effects on hippocampal cells (Raley-Susman et al, 1992), NGF:trkA interactions (Pitchford et al, 1995), D1 and D2 dopamine receptor action (Neve et al, 1992;Bouvier et al, 1993), m1 and m3 muscarinic receptor action (Baxter et al, 1994), ACh action on the Na ϩ /K ϩ ATPase (Miller et al, 1993), PKC action (Omary et al, 1992), cAMP effects on the H ϩ /K ϩ ATPase Thibodeau et al, 1994), glucocorticoid action (Redish et al, 1993), the role of PKC ⑀ on granulocyte-macrophagecolony-stimulating factor (GM-CSF) action (Wada et al, 1993), angiotensin II action (Dickinson et al, 1994), and CC-chemokine receptor action (Samson et al, 1996). The microphysiometer also has been used recently to examine the interactions between synthetic peptides and cognate receptors in an effort to design effective competitive inhibitors (Renschler et al, 1995).…”
Section: Bdnf Signal Transduction By Trkbt1 and Trkbt2: Microphysiomentioning
confidence: 99%
“…Pretreatment with 1 nM corticosterone, but not I tzM estradiol, progesterone, or testosterone, significantly decreased the acidification rate (56). These authors concluded that this inhibition was caused by decreased rates of glucose transport and protein synthesis in the cells, which are well established effects of glucocorticoids on fibroblasts.…”
Section: Applications Of Microphysiometrymentioning
confidence: 94%
“…Probably the greatest advantage of the microphysiometer is that, by measuring changes in metabolic rate, it is independent of the signal transduction pathway. The microphysiometer has therefore been used successfully to monitor activation of a wide variety of cell surface receptors that couple to different effectors, e.g., muscarinic M 1 , M 2 , M 3 , M 4 , and M 5 receptors (Wood et al 1999) or D2, D3, or D4 receptors (Coldwell et al 1999), intracellular targets such as nuclear hormone receptors (Redish et al 1993), and signal transduction pathways. The microphysiometer is particularly suited to study signal transduction pathways as activation or inhibition of a wide variety of effectors and transduction processes will affect metabolic rate.…”
Section: Principles Of Microphysiometrymentioning
confidence: 99%
“…The Cytosensor has been used to study the signal transduction pathways activated by a wide range of hormones, including corticotrophin-releasing factor (CRF; Barstye et al 1999;Robinson et al 1999;Smart et al 1999), parathyroid hormone (PTH; Barrett et al 1997), corticosterone (Redish et al 1993), estrogen (Redish et al 1993), interleukin-1 (IL-1; Hammond et al 1999;Smart et al 1998a), progesterone (Redish et al 1993), and testosterone (Redish et al 1993), as well as those signal transduction pathways activated by other neuropeptides, e.g., bombesin ) and the neurokinins (Jordan et al 1998).…”
Section: Microphysiometry and Signal Transductionmentioning
confidence: 99%